The street's chronicle traditional Chinese restaurant inspired by street style / Afrina Zulaikha Jasni ... [et al.] - Jasni, Afrina Zulaikha; Mustapha, Arnatul Aiza; Abd Rahaman, Nur Adila; Ahmad Noorhani, Nur Maizura (College of Built Environment, 2023)
This will serve traditional Chinese food while giving the customer experience Jalan Bunga Raya vibes during it's famous time.